Slot-coupled microstrip patch antennas - Chua, Kweng Yong. (2009)
The aperture-coupled microstrip antennas have been proposed recently, and are formulated in the spectral domain formulation using the reciprocity theorem. This feeding method for the microstrip antennas is well known for its excellence in bandwidth characteristics compared with other types of feeding. Here, we propose the use of another rigorous method , the so called the mixed potential integral equation (MPIE) which is formulated in spatial domain, to solve the aperture-coupled microstrip antennas problem.